IoT and big data analytics for smart cities : a global perspective - Rajendran, Sathiyaraj; Sabharwal, Munish; Ghinea, Gheorghita; Dhanaraj, Rajesh Kumar; Balusamy, Balamurugan (Boca Raton, FL : CRC Press, 2023)
"The book IoT and Big Data Analytics (IoT-BDA) for Smart Cities - A Global Perspective, emphasizes the challenges, architectural models, intelligent frameworks with smart decision- making systems using Big Data and IoT with case studies. The book illustrates the benefits of Big Data and IoT methods in framing smart systems for smart applications. The text is a coordinated amalgamation of research contributions and industrial applications in the field of smart cities"--
"A Chapman & Hall book" -- cover.
OCLC-licensed vendor bibliographic record.
Keywords: Smart cities; Internet of things; COMPUTERS / Database Management / Data Mining